2015
DOI: 10.5539/ies.v8n12p70
|View full text |Cite
|
Sign up to set email alerts
|

Self-Directed Learning and Skills of Problem-Based Learning: A Case of Nigerian Secondary Schools Chemistry Students

Abstract: The role of chemistry in the development of any society cannot be overemphasized. Chemistry students are therefore expected to acquire flexible knowledge and problem solving skills to facilitate the expected development of our modern society. The purpose of this article is to investigate the roles of teachers and student in the development of self-directed learning and skills in Nigerian Secondary Schools. PBL is a student-centered pedagogy which helps students develop problem solving skills and improved knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…During this study, both participants and the researcher played specific roles; for instance, as suggested by (Sze-yeng & Hussain, 2010) the teacher needed to become less of an authority figure and more of an active user with shared-power who interacted with other participants. This study also promoted the development of SDL within a collaborative learning environment, since there is evidence that both of these concepts can be blended effectively to develop learning (Abubakar & Arshad, 2015;Herman, 1983;Kelz, 2009;Mendieta et al, 2015). It has been found that, when individuals are engaged in cooperative learning activities, group work learning and self-learning are boosted if supported efficiently by facilitators who help students during the joint construction of conceptual knowledge (Fung & Lui, 2016).…”
Section: Self-directed Learningmentioning
confidence: 99%
“…During this study, both participants and the researcher played specific roles; for instance, as suggested by (Sze-yeng & Hussain, 2010) the teacher needed to become less of an authority figure and more of an active user with shared-power who interacted with other participants. This study also promoted the development of SDL within a collaborative learning environment, since there is evidence that both of these concepts can be blended effectively to develop learning (Abubakar & Arshad, 2015;Herman, 1983;Kelz, 2009;Mendieta et al, 2015). It has been found that, when individuals are engaged in cooperative learning activities, group work learning and self-learning are boosted if supported efficiently by facilitators who help students during the joint construction of conceptual knowledge (Fung & Lui, 2016).…”
Section: Self-directed Learningmentioning
confidence: 99%
“…Based on the results of data analysis and discussion of research results it can be concluded that problem-based learning can improve students' learning outcomes, it can be seen from the generic science skills of the experimental group taught by using the problem-based learning model is higher than the control group on addition, substitution, and elimination materials. (Abubakar & Arshad, 2015) their research found that problem-based learning has improved students' problem-solving skills and high order thinking skills. It is also in line with what has been found by (Zakiyah, 2014) that the application of PBL model can improve students' generic science skills by using some indicators, such as direct observation, indirect observation, the law of cause and effect, logical inference and logical framework.…”
Section: Conclusion and Suggestionsmentioning
confidence: 97%
“…In contrast to DL model, PBL model is a student-centered learning model in which students define their own key issues based on chemical bonding concepts for real-world problems through collaborative learning activities, also, direct students under the guidance of a teacher (Savoie & Andrew, 1994). Focusing on real-life problems and exploring relevant information allow students to develop their flexible knowledge and meaningful problem-solving skills (Abubakar & Arshad, 2015). PBL consists of the seven 7following steps: problem identification, knowledge exploration, hypothesis creation, key issue identification, independent study, re-evaluation, the application of new knowledge towards problem-solving, evaluation, and reflection (Prasad, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The motivational opportunity available in PBL is a real asset to students' motivation. Abubakar & Arshad (2015) concluded that students who learn using PBL have been able to develop a deeper understanding and acquire effective problem-solving skills as well as more effective and focus on independent information processing.…”
Section: Introductionmentioning
confidence: 99%